Pemikiran Ki Hajar Dewantara tentang Pendidikan yang Memerdekakan dan Implikasinya terhadap Sistem Pendidikan di SMP - Sa’ir Apipudin; Asep Muhammad Ilyas; Heri Kusnandar; Ricky Yoseptry (STKIP PGRI SITUBONDO, 2025)
This study aims to analyze the implementation of existentialist values in the educational process at SMP Negeri 8 Purwakarta. Existentialism is a philosophical movement that emphasizes individual freedom, responsibility, authenticity, and the search for meaning in life through conscious choices. In the era of modern education, particularly at the junior secondary school level, these values are highly relevant as students are in a critical phase of identity development. The study employs a qualitative approach with data collection techniques including observation, in-depth interviews, and document analysis. The findings indicate that existentialist values have emerged in several learning activities, although not yet evenly implemented. Freedom is reflected in the provision of choices in learning methods and the freedom to express opinions. Responsibility is evident in teachers’ emphasis on discipline, classroom agreements, and the consequences of each decision. Authenticity develops through teachers’ appreciation of the uniqueness of students’ opinions. Reflective activities conducted by some teachers help students understand the meaning of lessons in real-life contexts. However, the application of existentialist values has not yet become a comprehensive school culture. Some teachers remain focused on academic achievement and have not fully established spaces for intensive dialogue. Therefore, strengthening teacher capacity, implementing school policies that support reflective learning, and integrating existentialist principles into lesson planning are necessary. This study contributes to the development of a humanistic educational paradigm in Indonesia and serves as a reference for schools seeking to develop learning oriented toward the personal meaning of students.